Synthesis and characterization of novel heterobinuclear mercury(II)-DTPA-M(II) complexes: Electrocatalytic and sensor applications - Mishra G.K.; Krishna V.; Prakash R. (My University, 2025)
Hg(II) metal complex is synthesized using octadentate ligand diethylene triamine penta acetic acid (DTPA) and the interaction of second metal ions viz. Cu(II), Pb(II), Mg(II) and Ca(II) is studied for the formation of novel heterobinuclear complexes. Heterobinuclear complexes are formed by taking 1:1 ratio of metal ions with Hg(II)-DTPA in aqueous solution at pH above 7. Heterobinuclear Hg(II)-DTPA-M(II) complexes are characterized using electrochemical technique and stability constant is calculated by pH-titration technique. Electroactive and stable Hg(II)-DTPA-Pb(II) complex is found to be suitable for the electrocatalytic application and demonstrated for the detection of glutathione in the wide range of concentration from 10 g/L to 10 mg/L.